Model of Needs-Based Professionalism Development in Military Academy Magelang - Hartono, Untung; Rachman, Maman; RC, Achmad Rifai; Prihatin, Titi (Universitas Negeri Semarang, 2019)
Lecturers are professional educators and scientists whose main task is to transform, develop, and disseminate science, technology and art through education, research, and community service. Therefore, lecturers are required to possess pedagogical, personal, social, and professional competencies. Article 60, Law No. 14/2005 concerning Teachers and Lecturers, requires lecturers to